Social and economic crisis through the prism of Kondratiev long wave theory - Malešević, Matija (Sociološki pregled, 2022)
The scale of the modern economic crisis has refuted theories of a linear and self-regulating market. Adam Smith’s “invisible hand” turned out to be nothing but a myth which served the purpose of maintaining the monopoly. In pursuit of alternative interpretations, we have decided that this paper should investigate the scale of crisis in the world and how major powers respond to it, as seen through Kondratiev long wave theory. Initially, we present the basic theoretical presumptions, to which we added modern sociological interpretations. This section is followed by explanations of socio-technological factors which are crucial for the intervals of long waves. Finally, we give a general presentation of the relationship between major powers and their future geocultural strategies: This paper aims to fathom the mechanisms of structurally conditioned crises and to indicate the need to apply Kondratiev long-wave theory when creating highest-level strategic documents.